2021
DOI: 10.1097/yco.0000000000000722
|View full text |Cite
|
Sign up to set email alerts
|

Converging public health crises: substance use during the coronavirus disease 2019 pandemic

Abstract: Purpose of review The international, public health crisis caused by the rapid spread of SARS-CoV-2 has resulted in unforeseen medical and psychiatric consequences. We reviewed publications from January 2020 to January 2021, given that earlier documents were not relevant, to review findings on changes in substance use and overdoses during the pandemic. Additionally, this review of the literature also documents advocacy efforts, health service modification and challenges, as well as COVID-related he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Further investigation using other methodologies may aid in supporting this hypothesis. Moreover, given the growing evidence that the substance use epidemic has been exacerbated during this time, placing our findings into the broader environment of substance use disorder in WV during the COVID-19 pandemic is key ( Khoury, Preiss, Geiger, Anwar, & Conway, 2021 ; Niles, Gudin, Radcliff, & Kaufman, 2021 ; Striley & Hoeflich, 2021 ).…”
Section: Discussionmentioning
confidence: 93%
“…Further investigation using other methodologies may aid in supporting this hypothesis. Moreover, given the growing evidence that the substance use epidemic has been exacerbated during this time, placing our findings into the broader environment of substance use disorder in WV during the COVID-19 pandemic is key ( Khoury, Preiss, Geiger, Anwar, & Conway, 2021 ; Niles, Gudin, Radcliff, & Kaufman, 2021 ; Striley & Hoeflich, 2021 ).…”
Section: Discussionmentioning
confidence: 93%
“…Building on these limitations, future research may explore different mental health outcomes associated with these risk factors and self-compassion trajectories, including separately examining anxiety and depression symptoms, as well as exploring specific areas of difficulties such as eating disorders or substance use, both of which have increased drastically during the pandemic ( Striley and Hoeflich, 2021 ; Taquet et al, 2022 ). Additionally, although many of the variables in our study were required to be self-reported (e.g., self-compassion is theoretically only known by the respondent), future work involving observational or clinical assessments of mental health and health-related risk factors such as sleep quality or length may be helpful to increase the validity of these results.…”
Section: Discussionmentioning
confidence: 99%
“…Before and during the COVID-19 pandemic, the misuse and abuse of fentanyl appear to have persistently increased in the United States and elsewhere [ 11 ]. Overdose deaths and infections among people who use drugs, including fentanyl, increased during the COVID-19 crisis [ 12 14 ]. A study in Ontario, Canada, showed that fentanyl use increased by 108% among patients who were treated with opioid receptor agonists [ 15 ].…”
Section: Introductionmentioning
confidence: 99%